2019
DOI: 10.1186/s12985-019-1184-y
|View full text |Cite
|
Sign up to set email alerts
|

High sustained virologic response rates of sofosbuvir-based regimens in Chinese patients with HCV genotype 3a infection in a real-world setting

Abstract: Background Patients with hepatitis C virus (HCV) genotype 3 infection remain a difficult-to-cure population. This study evaluated the efficacy and safety of sofosbuvir-based regimen in genotype 3 patients in a real-world setting. Methods HCV genotype 3a-infected adults with compensated liver disease were treated with sofosbuvir (SOF)/velpatasvir (VEL) or SOF/daclatasvir (DCV) with or without ribavirin (RBV) for 12 or 24 weeks, respectively. Efficacy was measured by sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The expanding use of DAAs in clinical practice in recent years has provided an opportunity to assess their effectiveness and safety in real‐world cohorts, outside the controlled settings of clinical trials. Several real‐world cohorts have evaluated SOF/VEL effectiveness and safety in varying settings, with the results being similar to those of clinical trials 10,15‐24 …”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The expanding use of DAAs in clinical practice in recent years has provided an opportunity to assess their effectiveness and safety in real‐world cohorts, outside the controlled settings of clinical trials. Several real‐world cohorts have evaluated SOF/VEL effectiveness and safety in varying settings, with the results being similar to those of clinical trials 10,15‐24 …”
Section: Introductionmentioning
confidence: 83%
“…Several real-world cohorts have evaluated SOF/VEL effectiveness and safety in varying settings, with the results being similar to those of clinical trials. 10,[15][16][17][18][19][20][21][22][23][24] In this integrated real-world analysis, data from 12 clinical practice cohorts across different real-world settings in Canada, Europe and the USA were pooled to allow the evaluation of the real-world effectiveness of SOF/VEL for 12 weeks without ribavirin (based on the label or physician discretion) in the largest available heterogeneous HCV patient population and to investigate any patient characteristics affecting the risk of not achieving SVR. (Table 1)…”
Section: Introductionmentioning
confidence: 99%
“…27 Another real-world study from China showed that genotype 3a infected patients yield high and similar SVR12 rate in SOF/VEL and SOF + DCV ± RBV regimens. 28 However, the number of patients enrolled were small and the SVR12 rate on 3b sub-type with cirrhosis wasn't shown. In present study, patients with genotype 3 infection achieved SVR12 rates over 90% even high to 100% except for SOF + RBV and SOF/VEL regimens.…”
Section: Discussionmentioning
confidence: 99%
“…However, a considerable percentage of patients with HCV genotype 1 infection does not respond to IFN-RBV therapy due to drug resistance and/or poor tolerability. In treatment with direct-acting antivirals (DAA), the SVR rates may exceed 80% irrespective of genotype though an interferon-based therapy may be still beneficial in DAAresistant patients [40][41][42][43]. HCV has been involved in the triggering of autoimmune diseases with the development of mostly non-organ-specific autoantibodies (NOSA), and this was associated with a more severe histological and biochemical profile of hepatitis C infection [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%